Lithium ion battery electrolyte additive and electrolyte
By using 2-(dimethylphosphate)-18-crown-6-ether additive in the lithium-ion battery electrolyte, the performance problems of the electrolyte in high energy density and low temperature environments are solved, and the results of improving conductivity, reducing viscosity, enhancing stability and improving safety are achieved.
Patent Information
- Application Number
- CN202411646909.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing lithium-ion battery electrolytes exhibit reduced conductivity, increased viscosity, poor chemical stability, poor thermal stability, insufficient compatibility of positive and negative electrodes and high safety risks under high energy density and low temperature environments.
2-(dimethylphosphate)-18-crown-6-ether is used as an electrolyte additive to promote dissociation of lithium salts and reduce electrolyte viscosity through its crown ether group, and use phosphate groups to provide flame retardant effects, improve electrochemical windows and increase solvent stability.
It improves the conductivity of the electrolyte, reduces viscosity, enhances chemical and thermal stability, improves the compatibility and safety performance of positive and negative electrodes, and improves the high energy density and low temperature performance of lithium-ion batteries.
Smart Images

Figure BDA0005139902390000061 
Figure BDA0005139902390000111 
Figure BDA0005139902390000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a high energy density lithium ion battery electrolyte, and in particular to the application of 2-(dimethyl phosphate)-18-crown-6-ether in the electrolyte. Background Art
[0002] With the global emphasis on environmental protection and sustainable development, the electric vehicle (EV) market is growing rapidly. In order to increase the range of electric vehicles and enable them to compete with traditional fuel vehicles in terms of ease of use, the energy density of lithium-ion batteries needs to be improved. As a key component of lithium-ion batteries, the performance of electrolytes directly affects the energy density of batteries. For example, electric vehicles with long range require batteries to store more energy within a limited volume and weight, which places higher requirements on electrolytes.
[0003] Portable electronic devices such as smartphones, tablets and laptops are constantly pursuing thinner and lighter designs and longer battery life. Consumers want their devices to work longer without increasing the size and weight of the device. High-energy-density lithium-ion batteries are the key to meeting this demand, and innovation in electrolytes is essential to achieving increased battery energy density. For example, in smartphones, batteries with higher energy density can reduce charging frequency and improve user experience.
[0004] Electrolyte plays an important role in transporting lithium ions in lithium-ion batteries. Theories such as the solvation structure and migration mechanism of lithium ions in electrolytes are the basis for designing high-energy-density electrolytes. For example, understanding how lithium ions interact with solvent molecules and lithium salt anions in the electrolyte helps to select a suitable combination of solvent and lithium salt to increase the migration rate of lithium ions. Studies have shown that by adjusting the dielectric constant and electron-donating ability of the solvent, the solvation sheath of lithium ions can be optimized, thereby improving its transport efficiency in the electrolyte.
[0005] The electrolyte must have sufficient electrochemical stability to prevent oxidative or reductive decomposition within the operating voltage range of the battery. Theoretically, the redox potential window of the electrolyte determines the highest and lowest operating voltages that the battery can reach. High energy density batteries often require higher operating voltages, which requires the electrolyte to have a wider electrochemical stability window. For example, in high-voltage lithium-ion batteries, the electrolyte needs to be stable at voltages above 4.5V, which involves the selection and optimization of solvents, lithium salts and additives in the electrolyte to improve its oxidative stability.
[0006] Current lithium-ion battery electrolytes are mainly based on a combination of carbonate solvents (such as ethylene carbonate, diethyl carbonate, etc.) and lithium salts (such as lithium hexafluorophosphate). This traditional electrolyte meets the needs of existing lithium-ion batteries to a certain extent, but has limitations in terms of energy density. For example, lithium hexafluorophosphate is easily decomposed under high voltage, which limits the further improvement of the battery's operating voltage and energy density.
[0007] In the research and development of high-energy-density power lithium-ion battery electrolytes, major chemical companies, battery manufacturers and scientific research institutions around the world are actively competing. For example, Japanese companies are in a leading position in the early research and development of lithium-ion battery electrolytes, and companies such as Mitsubishi Chemical have deep accumulation in the research and development of basic electrolyte formulas. In recent years, Chinese and Korean companies and research institutions have made considerable progress in the research and development and industrialization of new electrolyte materials. Chinese companies such as Tianci Materials and Xinzhoubang have continuously expanded their share of the electrolyte market and are actively investing in the research and development of high-energy-density electrolytes.
[0008] As mentioned above, increasing the operating voltage of batteries is an important way to increase energy density, but existing electrolytes are prone to decomposition under high voltages, which not only leads to a decline in battery performance, but may also cause safety hazards.
[0009] High energy density batteries often perform poorly in low temperature environments. The viscosity of the electrolyte increases significantly as the temperature decreases, making lithium ion transmission difficult. Improving the low temperature performance of the electrolyte so that it can still maintain good ion conductivity at low temperatures is a technical problem that needs to be solved urgently.
[0010] As energy density increases, battery safety risks also increase. The electrolyte may burn or explode under abnormal conditions such as overcharge, overdischarge, short circuit or high temperature. Therefore, while increasing energy density, ensuring the safety of the electrolyte, such as improving its flame retardancy and inhibiting the growth of lithium dendrites, is also an important challenge.
[0011] There are currently existing technologies for the technical problems to be solved. For example, CN116344943A discloses a lithium iron manganese phosphate battery electrolyte, a secondary battery and electrical equipment. The components of the lithium iron manganese phosphate battery electrolyte are: lithium salt: selected from lithium hexafluorophosphate, lithium tetrafluoroborate and other types; organic solvent: including ethylene carbonate, propylene carbonate and other types; additives: including crown ether compounds and boron trifluoride-pyridine, and may also include vinylene carbonate. Each additive has a certain mass percentage content range in the electrolyte. The secondary battery includes a positive electrode plate, a negative electrode plate (made of graphite, etc.), a separator and the above-mentioned electrolyte. The electrolyte includes lithium salts, solvents and additives, which can well solve the problems of high temperature cycle and poor storage performance of LMFP batteries. The additives include crown ether compounds, which can significantly reduce the residual amount of Mn ions in the electrolyte. Because of the strong coordination environment in its structure, it can form a complex with Mn ions, which can well inhibit the migration of dissolved Mn ions in the solution, effectively remove Mn ions in the electrolyte, and improve the thermal stability of the electrolyte. In addition, the selection of additives containing Si-N characteristic structures can remove HF, and combined with the synergistic effect of low-impedance additives, the battery cycle performance is comprehensively improved, while the interface impedance is reduced and the conductivity is improved. However, in the prior art, crown ethers or phosphates are added to the electrolyte alone, which plays a corresponding role, but also brings corresponding performance risks, as described below.
[0012] Advantages of crown ethers: Adding crown ethers to lithium-ion battery electrolytes can improve the conductivity of the electrolyte, mainly for the following two reasons: (1) Promoting the dissociation of lithium salts: The lithium salts in lithium-ion battery electrolytes need to dissociate into lithium ions and anions in order to achieve charge conduction. In ordinary electrolytes, lithium salts may have a certain degree of association, which will limit the number of lithium ions and reduce the conductivity of the electrolyte. Crown ethers have a special ring structure, the size of the holes inside them matches the size of lithium ions, and can selectively complex with lithium ions. This complexation can destroy the association structure of lithium salts, allowing more lithium salts to dissociate into free lithium ions and anions, thereby increasing the number of mobile charges in the electrolyte and improving the conductivity. (2) Reducing electrolyte viscosity: The viscosity of the electrolyte has an important influence on the migration speed of ions. The higher the viscosity, the greater the resistance to the movement of ions in the electrolyte and the lower the conductivity. The addition of crown ethers can interact with the solvent molecules in the electrolyte, change the structure and arrangement of the solvent molecules, and reduce the overall viscosity of the electrolyte. In this way, lithium ions can move more freely in low-viscosity electrolytes, speeding up the transfer of charge and thus improving the conductivity of the electrolyte. However, crown ethers also have performance risks: (1) Crown ethers have poor thermal stability when used in lithium-ion battery electrolytes. ① Instability of macrocyclic structure: Crown ethers are macrocyclic compounds containing multiple oxygen atoms. This macrocyclic structure itself is prone to conformational changes or structural distortion when heated. The flexibility of the macrocyclic structure makes the molecule more likely to deform under heat, causing stress on the chemical bonds within the molecule, which in turn reduces the thermal stability of the crown ether molecule. ② Influence of oxygen atoms: Crown ether molecules contain multiple oxygen atoms, which have high electronegativity and are easy to attract surrounding electrons. When heated, the distribution of the electron cloud on the oxygen atom will change. This redistribution of the electron cloud will make the chemical bonds within the molecule unstable and prone to breakage, thereby reducing the thermal stability of the crown ether. ③ Thermal sensitivity of the complex structure: Crown ethers can react with lithium ions to form complexes. This complex structure will be affected by heat because the complex bond between lithium ions and crown ethers is not very strong and is easy to break at high temperatures. When the complex bond breaks, lithium ions will be released, and the structure of the crown ether molecule will be destroyed, resulting in a decrease in thermal stability. ④ The influence of energy change: The complexation of crown ethers with lithium ions is a process of energy change, and a certain amount of energy will be absorbed or released during the complexation process. When heated, this energy change will intensify, causing the interaction between crown ethers and lithium ions to change, thereby affecting the thermal stability of crown ethers. (2) The application of crown ethers in lithium-ion battery electrolytes leads to poor SEI or CEI film formation. ① Interference with lithium ion transmission: Crown ethers have a strong complexing ability for lithium ions and will form complexes with lithium ions in the electrolyte. This complexation may interfere with the transmission of lithium ions on the electrode surface, resulting in uneven concentration distribution of lithium ions on the electrode surface.In the formation process of SEI or CEI film, lithium ions need to participate in the reaction to form a stable film structure, and the complexation of lithium ions by crown ethers reduces the number of lithium ions participating in the film formation reaction or slows down the transmission speed, thereby affecting the normal growth and formation of the film and making the film formation effect worse. ② Uneven film composition: The complex of crown ether and lithium ions may be embedded in the forming SEI or CEI film, resulting in uneven film composition. This uneven film structure may not effectively protect the electrode material during the charge and discharge process of the battery, and is prone to rupture or decomposition, thereby affecting the performance and life of the battery. ③ Solvent competition reaction: Crown ethers interact with solvent molecules in the electrolyte and may compete for reaction sites involved in the formation of SEI or CEI films. For example, in the initial reaction stage on the electrode surface, the reduction reaction of solvent molecules is an important step in the formation of SEI film. The presence of crown ethers may interfere with the adsorption and reaction of solvent molecules on the electrode surface, making it impossible for solvent molecules to participate in the formation of the film normally, resulting in unsatisfactory film formation.
[0013] In contrast, phosphate esters have the following advantages: (1) Phosphate esters can have a flame retardant effect when used in electrolytes. ① Phosphate esters will produce phosphorus-containing free radicals, such as PO·, during the thermal decomposition process. These free radicals can capture hydrogen radicals (H·) and hydroxyl radicals (HO·) produced during the combustion reaction of the electrolyte and convert them into relatively stable substances, such as HPO, thereby preventing or slowing down the combustion chain reaction, interrupting the free radical reaction chain on which the flame continues to burn, and achieving a flame retardant effect. ② Phosphate esters absorb a large amount of heat during decomposition and related chemical reactions, which can reduce the temperature of the electrolyte system and make it difficult for battery materials to reach the temperature conditions required for combustion, thereby inhibiting the occurrence of combustion reactions. At the same time, the presence of phosphoric acid will prevent carbon monoxide (CO) from being oxidized to carbon dioxide (CO2). This process will also consume heat and further reduce the temperature of the system. (2) Improve the electrochemical window. The electrochemical window refers to the highest and lowest potential ranges in which redox reactions can occur in the electrolyte. Adding phosphate esters can improve the electrochemical window of the electrolyte, allowing it to undergo stable redox reactions over a wider potential range. A wider electrochemical window means that the battery can operate at a higher voltage, thereby increasing the battery's energy density; at the same time, it can maintain good stability at a lower voltage, reducing the risk of damage to the battery under overcharge or over-discharge conditions. (3) Increase solvent stability. Phosphate esters have high chemical and thermal stability in electrolytes. They can react with water molecules in the electrolyte to form phosphates and esters, thereby reducing the content of water molecules. This helps to reduce the evaporation rate and decomposition rate of the electrolyte, improve the stability of the battery in harsh environments such as high temperature, and extend the battery's cycle life. In addition, this improvement in stability is also conducive to the battery maintaining good performance during long-term storage. (4) Assist in the formation of a stable interface film. On the surface of the positive and negative electrodes of the battery, a solid electrolyte interface (SEI) film and a positive electrode electrolyte interface (CEI) film are formed. Phosphate esters can participate in the formation process of these interface films, or adjust their structure and composition to make them more stable and have good ionic conductivity and electronic insulation. A stable interface film can prevent the continuous decomposition of the electrolyte, inhibit the dissolution of positive electrode metal ions, and improve the battery's cycle performance and safety. Phosphate esters also have some performance risks: (1) Reduced ion conductivity: The molecular structure and properties of phosphate esters may affect the migration rate of lithium ions in the electrolyte. Compared with conventional electrolyte solvents, phosphate esters generally have a higher viscosity, which increases the transport resistance of ions in the electrolyte and causes a decrease in ionic conductivity. The decrease in ionic conductivity will increase the internal resistance of the battery, generate more heat during the charge and discharge process, and affect the power performance and energy efficiency of the battery. (2) Impact on lithium salts: Phosphate esters may interact with lithium salts in the electrolyte, affecting the dissolution and ionization of lithium salts, thereby affecting the capacity of the battery.For example, phosphate esters may form complexes or precipitate with lithium salts, reducing the effective concentration of lithium salts and the number of lithium ions involved in the charge and discharge reaction, resulting in a decrease in battery capacity. (3) Increased freezing point: The molecular structure of phosphate esters makes them less fluid at low temperatures, and they are prone to solidification or crystallization, which increases the freezing point of the electrolyte. In a low-temperature environment, the solidification of the electrolyte will seriously affect the transmission of lithium ions, causing a significant decrease in the low-temperature performance of the battery, including a decrease in discharge capacity, a decrease in the discharge voltage platform, and an increase in internal resistance.
[0014] At the same time, in the field of electrolyte additive research, researchers are accustomed to making improvements in similar or similar functional compounds. However, the performance and reaction conditions of crown ethers and phosphates are very different. For example, the synthesis of crown ethers requires specific cyclization reaction conditions, and phosphates have their own esterification requirements. Combining the two requires not only precise design of molecular structure and functional group connection methods, but also appropriate reaction conditions. Any slight deviation will not only fail to achieve functional fusion, but also produce negative effects. That is, ensuring that the above functional groups are accurately formed and stably connected is a huge challenge that requires overcoming technical obstacles; there is no similar technical route in the existing technology.
[0015] The present invention aims to solve the technical problems faced by high energy density lithium ion battery electrolytes, mainly involving the following aspects:
[0016] (1) Improve electrical conductivity: In order to meet the fast charging and discharging requirements of high energy density batteries, the electrolyte needs to have a high ionic conductivity. However, the ionic conductivity of traditional electrolyte systems decreases under conditions such as high electrolyte concentration or low temperature.
[0017] (2) Reduce viscosity: High viscosity electrolyte will increase the resistance to ion migration and reduce the charge and discharge performance of the battery. Especially in low temperature environment, the viscosity of the electrolyte will increase significantly, resulting in a significant decrease in battery performance.
[0018] (3) Chemical stability: In high energy density batteries, electrode materials have a high operating voltage and strong activity, and are prone to chemical reactions with the electrolyte. For example, high nickel cathode materials will accelerate the oxidation and decomposition of the electrolyte under high voltage, affecting the cycle life and safety of the battery.
[0019] (4) Thermal stability: High energy density batteries generate a lot of heat during the charging and discharging process, which increases the internal temperature of the battery. If the thermal stability of the electrolyte is poor, dangerous situations such as decomposition and combustion may occur at high temperatures.
[0020] (5) Positive electrode compatibility: The positive electrode materials of high energy density batteries usually have a high specific surface area and activity, and are prone to interfacial reactions with the electrolyte, resulting in structural damage and performance degradation of the positive electrode surface. For example, high nickel ternary positive electrode materials will react with the electrolyte during the cycle, generating gas and causing the battery to swell.
[0021] (6) Negative electrode compatibility: For high-capacity negative electrode materials such as silicon-based negative electrodes, huge volume changes will occur during the charging and discharging process, which can easily lead to the rupture and reconstruction of the SEI film (solid electrolyte interface film) on the negative electrode surface, consume a large amount of electrolyte, and reduce the cycle life of the battery. Summary of the invention
[0022] The present invention aims to solve the problems of high energy density lithium-ion battery electrolyte, including improving conductivity to meet charging and discharging requirements, reducing viscosity to reduce ion migration resistance (especially at low temperatures), enhancing chemical stability, improving thermal stability, improving positive and negative electrode compatibility, reducing interface reactions and SEI film rupture, etc., to ensure battery performance and safety and promote the development of lithium-ion battery technology.
[0023] Specifically, the present invention provides an electrolyte additive; the additive is 2-(dimethylphosphonate)-18-crown-6-ether as shown in Formula I:
[0024]
[0025] The synthesis method of the lithium-ion battery electrolyte additive comprises the following steps: adding 18-crown-6-ether, N-bromosuccinimide and carbon tetrachloride into a dry reaction flask; then adding an initiator; heating the reaction mixture to reflux under nitrogen protection; during the reaction, N-bromosuccinimide generates bromine free radicals under the action of the initiator, and the bromine free radicals selectively react with a carbon on 18-crown-6-ether to generate 18-crown-6-ether-Br and succinimide; adding 18-crown-6-ether-Br into a dry reaction flask; , potassium dimethyl phosphate, a phase transfer catalyst and an organic solvent; under stirring, heating the reaction mixture to 60-80°C for reaction; under the action of the phase transfer catalyst, the phosphate anion in the potassium dimethyl phosphate reacts with the bromine atom in 18-crown-6-ether-Br to undergo nucleophilic substitution reaction to generate 2-(dimethyl phosphate)-18-crown-6-ether and potassium bromide; after the reaction is completed, cooling the reaction mixture to room temperature; extracting and combining the organic phases, drying and purifying to obtain pure 2-(dimethyl phosphate)-18-crown-6-ether.
[0026] Furthermore, the initiator is azobisisobutyronitrile; the phase transfer catalyst is tetrabutylammonium bromide; the molar ratio of 18-crown-6-ether-Br to dimethyl phosphate potassium salt is 1:1.1-1.2, and the amount of the phase transfer catalyst is 0.1-0.2 times the amount of 18-crown-6-ether-Br substance.
[0027] Further, purification was carried out by column chromatography: silica gel was selected as the stationary phase, ethyl acetate-petroleum ether mixed solvent was selected as the eluent, the ratio of the two was adjusted (1:5-1:3), and monitored by TLC, and the fractions containing the target product were collected to obtain pure 2-(dimethylphosphate)-18-crown-6-ether.
[0028] For example, the synthesis method of 2-(dimethylphosphonate)-18-crown-6-ether can be as follows:
[0029] (1) 18-crown-6-ether (high purity, dried), N-bromosuccinimide (NBS), azobisisobutyronitrile (AIBN) as initiators, and carbon tetrachloride (CCl4) as solvent.
[0030] (2) Add 18-crown-6-ether, N-bromosuccinimide and carbon tetrachloride to a dry reaction flask. The molar ratio of 18-crown-6-ether to N-bromosuccinimide is 1:1.1. Then add a small amount of azobisisobutyronitrile (the molar fraction relative to 18-crown-6-ether is about 0.05-0.1).
[0031] (3) Under nitrogen protection, the reaction mixture is heated to reflux. During the reaction, N-bromosuccinimide generates bromine free radicals under the initiation of AIBN, and the bromine free radicals selectively react with a carbon on 18-crown-6-ether to generate a brominated product of 18-crown-6-ether and succinimide. The reaction equation is: 18-crown-6-ether + NBS → 18-crown-6-ether-Br + succinimide. Reflux for 3-6 hours.
[0032] (4) dimethyl phosphate potassium salt (can be prepared by reacting dimethyl phosphate with potassium hydroxide), a phase transfer catalyst (tetrabutylammonium bromide, TBAB), and an organic solvent (dimethylformamide, DMF).
[0033] (5) In a dry reaction flask, 18-crown-6-ether-Br, dimethyl phosphate potassium salt, a phase transfer catalyst and an organic solvent are added. The molar ratio of 18-crown-6-ether-Br to dimethyl phosphate potassium salt is 1:1.1-1.2, and the amount of the phase transfer catalyst is 0.1-0.2 times the amount of the 18-crown-6-ether-Br substance.
[0034] (6) The reaction mixture is heated to 60-80°C under stirring to react. Under the action of a phase transfer catalyst, the phosphate anion in the potassium dimethyl phosphate reacts with the bromine atom in 18-crown-6-ether-Br to undergo a nucleophilic substitution reaction to generate 2-(dimethyl phosphate)-18-crown-6-ether and potassium bromide. The reaction equation is: 18-crown-6-ether-Br+(CH3O)2PO2K→2-(dimethyl phosphate)-18-crown-6-ether+KBr. The reaction time is 12-24 hours.
[0035] (7) After the reaction is completed, the reaction mixture is cooled to room temperature.
[0036] (8) Then pour into a large amount of water and extract the product with an organic solvent (dichloromethane). Extract 3-5 times, and the amount of organic solvent used each time is about 1 / 3-1 / 2 of the volume of the aqueous phase.
[0037] (9) Combine the organic phases and wash with saturated brine 2-3 times to remove residual water-soluble impurities.
[0038] (10) Dry the organic phase over anhydrous sodium sulfate overnight and filter to remove the desiccant.
[0039] (11) The organic solvent was removed by rotary evaporation to obtain a crude product.
[0040] (12) The crude product was purified by column chromatography. Silica gel was selected as the stationary phase, and an ethyl acetate-petroleum ether mixed solvent was selected as the eluent. The volume ratio of ethyl acetate and petroleum ether was adjusted to 1:5-1:3. The mixture was monitored by TLC, and the fractions containing the target product were collected to obtain pure 2-(dimethylphosphonate)-18-crown-6-ether.
[0041] The present invention relates to a high energy density lithium ion battery electrolyte containing 2-(dimethyl phosphate)-18-crown-6-ether. The components of the electrolyte include lithium salt, an anhydrous organic solvent and an electrolyte additive; wherein the electrolyte additive includes 2-(dimethyl phosphate)-18-crown-6-ether; the amount of 2-(dimethyl phosphate)-18-crown-6-ether in the electrolyte is 0.1%-10%, preferably 0.1%-5%, and further preferably 0.1%-2% of the total mass of the electrolyte.
[0042] Different from the above-mentioned prior art, the 2-(dimethylphosphate)-18-crown-6-ether proposed in the present invention introduces a phosphate functional group on the basis of the crown ether. In practical applications, the crown ether group in 2-(dimethylphosphate)-18-crown-6-ether can promote the dissociation of lithium salts, reduce the viscosity of the electrolyte, and thus improve the conductivity of the electrolyte. The phosphate group in 2-(dimethylphosphate)-18-crown-6-ether can have a flame retardant effect, while improving the electrochemical window, increasing the solvent stability, and assisting in the formation of a stable interface film.
[0043] Furthermore, the present invention provides a high energy density lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether, wherein the additive accounts for 0.1% to 20% of the total mass of the lithium ion battery electrolyte.
[0044] Preferably, in addition to 2-(dimethylphosphate)-18-crown-6-ether, the other additives are selected from at least one of fluoroethylene carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methanedisulfonic acid methylene ester, tris(trimethylsilyl)phosphate, 1,3-propylene sultone, ethoxypentafluorocyclotriphosphazene, tetravinylsilane, fluorobenzene, tripropargyl phosphate, dicyclohexylcarbodiimide, lithium difluorophosphate, lithium difluorooxalatoborate, and lithium difluorobisoxalatephosphate.
[0045] Furthermore, the present invention provides a high energy density lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether, wherein the concentration of lithium salt in the electrolyte is 0.8M-1.4M.
[0046] Preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
[0047] Furthermore, the present invention provides a high energy density lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether, wherein the anhydrous organic solvent in the electrolyte accounts for 60% to 80% of the total mass of the lithium ion battery electrolyte.
[0048] Preferably, the anhydrous organic solvent includes any one of carbonates and fluorinated solvents or a mixture of two or more thereof.
[0049] Preferably, the carbonate mainly includes propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate and ethylene carbonate.
[0050] Preferably, the fluorinated solvent mainly includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl trifluoroethyl carbonate, di(2,2,2-trifluoroethyl) carbonate, difluoroethylene carbonate, and difluoro(2,2-difluoroethyl) carbonate.
[0051] In the additive structure of the present invention, the introduction of phosphate groups improves the problems of poor thermal stability and poor film-forming effect of crown ethers. Reasons and mechanisms: (1) Enhanced structural rigidity: The introduction of phosphate groups will change the original molecular structure of crown ethers. The phosphate groups have a certain rigid structure. After being connected to the crown ether macrocyclic structure, they limit the conformational changes and structural distortion capabilities of the crown ether macrocyclic ring. This structural restriction reduces the stress on the chemical bonds within the crown ether molecule when it is heated, thereby improving the overall thermal stability of the molecule. (2) Regulation of electronic effects: The phosphate group has a unique electron cloud distribution. When connected to the crown ether, it can adjust the electron cloud around the oxygen atom in the crown ether molecule. Due to the presence of the phosphate group, the original situation of the oxygen atom in the crown ether molecule changing its energy level when heated alone is changed. During the heating process, the phosphate group shares the influence of part of the electron cloud redistribution, thereby improving the stability of the chemical bonds within the crown ether molecule and reducing the possibility of chemical bond breakage due to changes in the electron cloud of the oxygen atom. (3) Improved complex stability: After the introduction of the phosphate group, the complex structure of the crown ether and lithium ions changes. The phosphate group may interact with lithium ions to a certain extent. This interaction cooperates with the complexation of the crown ether to lithium ions, so that the crown ether-lithium ion-phosphate forms a more stable composite structure. When heated, the complex bonds in this composite structure are relatively difficult to break, which reduces the damage to the crown ether molecular structure caused by the breakage of the complex bonds, thereby improving thermal stability. At the same time, in the process of energy change, due to the presence of the phosphate group, the absorption and release of energy in the new composite structure are more stable, reducing the impact of energy change on the interaction between the crown ether and lithium ions. (4) Optimization of lithium ion transport: The introduction of the phosphate group changes the complexation mode of the crown ether to lithium ions. On the one hand, the phosphate group may have a moderate interaction with lithium ions, reducing the excessive complexation of the crown ether to lithium ions alone. This makes the number of freely movable lithium ions in the electrolyte relatively increase, and the concentration distribution of lithium ions on the electrode surface is more uniform, which is conducive to the participation of lithium ions in the reaction during the formation of SEI or CEI films, improves the uniformity of film growth and formation, and improves the film formation effect. (5) Since the phosphate group changes the complexation state between the crown ether and lithium ions, the crown ether-lithium ion complex is less embedded in the SEI or CEI membrane. At the same time, the phosphate group itself may participate in the membrane formation process, which can have better compatibility with other components in the membrane, making the composition of the membrane more uniform. This uniform membrane structure can more effectively protect the electrode material during the battery charging and discharging process, and improve the performance and life of the battery.
[0052] Beneficial effects:
[0053] The present invention introduces a phosphate functional group on the basis of crown ether to synthesize a 2-(dimethyl phosphate)-18-crown-6-ether. In the additive structure, due to the introduction of the phosphate group, the problems of poor thermal stability and poor film-forming effect of the crown ether are improved. In the application of lithium-ion battery electrolyte, the crown ether group in 2-(dimethyl phosphate)-18-crown-6-ether can promote the dissociation of lithium salts, reduce the viscosity of the electrolyte, and thus improve the conductivity of the electrolyte; the phosphate group in 2-(dimethyl phosphate)-18-crown-6-ether can play a flame retardant effect, while improving the electrochemical window, increasing the solvent stability, and assisting in the formation of a stable interface film.
[0054] Experiments show that adding 2-(dimethylphosphate)-18-crown-6-ether to the electrolyte of a high-energy-density lithium-ion battery for use in lithium-ion batteries can improve their initial efficiency, rate performance, high and low-temperature discharge performance at -30°C to 55°C, storage performance, cycle performance and safety performance during operation, and has a good application prospect in high-energy-density systems.
[0055] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0056] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0057] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0058] The structure of the additive 2-(dimethylphosphonate)-18-crown-6-ether is as follows:
[0059]
[0060] The synthesis method of 2-(dimethylphosphonate)-18-crown-6-ether is:
[0061] (1) 18-crown-6-ether (high purity, dried), N-bromosuccinimide (NBS), azobisisobutyronitrile (AIBN) as initiators, and carbon tetrachloride (CCl4) as solvent.
[0062] (2) Add 18-crown-6-ether, N-bromosuccinimide and carbon tetrachloride to a dry reaction flask. The molar ratio of 18-crown-6-ether to N-bromosuccinimide is 1:1.1. Then add a small amount of azobisisobutyronitrile (molar fraction relative to 18-crown-6-ether is 0.08).
[0063] (3) Under nitrogen protection, the reaction mixture is heated to reflux. During the reaction, N-bromosuccinimide generates bromine free radicals under the initiation of AIBN, and the bromine free radicals selectively react with a carbon on 18-crown-6-ether to generate a brominated product of 18-crown-6-ether and succinimide. The reaction equation is: 18-crown-6-ether + NBS → 18-crown-6-ether-Br + succinimide. Reflux for 3-6 hours.
[0064] (4) dimethyl phosphate potassium salt (can be prepared by reacting dimethyl phosphate with potassium hydroxide), a phase transfer catalyst (tetrabutylammonium bromide, TBAB), and an organic solvent (dimethylformamide, DMF).
[0065] (5) In a dry reaction flask, 18-crown-6-ether-Br, dimethyl phosphate potassium salt, a phase transfer catalyst and an organic solvent are added. The molar ratio of 18-crown-6-ether-Br to dimethyl phosphate potassium salt is 1:1.2, and the amount of the phase transfer catalyst is 0.2 times the amount of the 18-crown-6-ether-Br substance.
[0066] (6) The reaction mixture is heated to 60-80°C under stirring to react. The phosphate anion in the potassium dimethyl phosphate reacts with the bromine atom in 18-crown-6-ether-Br under the action of a phase transfer catalyst to generate 2-(dimethyl phosphate)-18-crown-6-ether and potassium bromide. The reaction equation is: 18-crown-6-ether-Br+(CH3O)2PO2K→2-(dimethyl phosphate)-18-crown-6-ether+KBr. The reaction time is 22 hours.
[0067] (7) After the reaction is completed, the reaction mixture is cooled to room temperature.
[0068] (8) Then pour into a large amount of water and extract the product with an organic solvent (dichloromethane). Extract 3-5 times, and the amount of organic solvent used each time is about 1 / 2 of the volume of the aqueous phase.
[0069] (9) The organic phases were combined and washed three times with saturated brine to remove residual water-soluble impurities.
[0070] (10) Dry the organic phase over anhydrous sodium sulfate overnight and filter to remove the desiccant.
[0071] (11) The organic solvent was removed by rotary evaporation to obtain a crude product.
[0072] (12) The crude product was purified by column chromatography. Silica gel was selected as the stationary phase, and a mixed solvent of ethyl acetate and petroleum ether was selected as the eluent. The ratio of the two was adjusted to 1:5. The mixture was monitored by TLC, and the fractions containing the target product were collected to obtain pure 2-(dimethylphosphonate)-18-crown-6-ether.
[0073] Example
[0074] The positive electrode active material of the lithium ion battery used in the embodiment of the present invention is a ternary material (LiNi0.8Co0.1Mn0.1O4), the negative electrode material is artificial graphite, and the electrolyte usage is 2.3±0.5g / Ah. A lithium ion battery assembled with a high energy density lithium ion battery electrolyte containing 2-(dimethyl phosphate)-18-crown-6-ether is selected as an embodiment, and a lithium ion battery assembled with a conventional electrolyte without 2-(dimethyl phosphate)-18-crown-6-ether is selected as a comparative example.
[0075] The specific steps for preparing the electrolyte in the glove box (H2O < 5ppm) are as follows:
[0076] (1) dehydrating an anhydrous organic solvent molecular sieve under the protection of nitrogen or inert gas to obtain an anhydrous organic solvent;
[0077] (2) adding an appropriate amount of lithium salt to an anhydrous organic solvent, stirring and cooling to obtain a mixed solution;
[0078] (3) Add appropriate amount of additives to the mixed solution to obtain 2000 g of electrolyte, which is placed in a fluorination bottle.
[0079] The electrolyte is used to assemble a lithium-ion battery. The positive electrode material of the lithium-ion battery is a ternary material (LiNi0.8Co0.1Mn0.1O4), the negative electrode material is artificial graphite, the designed capacity is 60Ah, and the injection amount is 2.3±0.5g / Ah.
[0080] The electrolyte formulation is shown in the following comparative examples or embodiments.
[0081] Comparative Example 1:
[0082] The anhydrous organic solvent used is: diethyl carbonate: ethyl methyl carbonate: ethylene carbonate = 30:40:30; lithium salt: the concentration is 1.2M lithium hexafluorophosphate (LiPF6).
[0083] Comparative Example 2:
[0084] The anhydrous organic solvent used is: diethyl carbonate: ethyl methyl carbonate: ethylene carbonate = 30:40:30; lithium salt: concentration is 0.8M lithium hexafluorophosphate (LiPF6), concentration is 0.4M lithium bis(fluorosulfonyl)imide (LiFSI).
[0085] Comparative Example 3:
[0086] The anhydrous organic solvent used is: diethyl carbonate: ethyl methyl carbonate: ethylene carbonate = 30:40:30; lithium salt: concentration is 0.8M lithium hexafluorophosphate (LiPF6), concentration is 0.4M lithium bis(fluorosulfonyl)imide (LiFSI). Additives: 0.5% lithium difluorooxalatoborate, 0.5% lithium difluorophosphate, 0.3% lithium difluorobis(oxalatophosphate), 0.3% vinylene carbonate, 0.5% 1,3-propane sultone, 0.5% fluoroethylene carbonate, 1% vinyl sulfate, 0.5% tris(trimethylsilyl)phosphate, 0.5% methylene disulfonate (the above percentages are the percentages of the corresponding additives in the total mass of the lithium-ion battery electrolyte, the same below).
[0087] Embodiment 1:
[0088] The anhydrous organic solvent used is: diethyl carbonate: ethyl methyl carbonate: ethylene carbonate = 30:40:30; lithium salt: 0.8M lithium hexafluorophosphate (LiPF6), 0.4M lithium bis(fluorosulfonyl)imide (LiFSI). Additives: 0.5% lithium difluorooxalatoborate, 0.5% lithium difluorophosphate, 0.3% lithium difluorobis(oxalatophosphate), 0.3% vinylene carbonate, 0.5% 1,3-propane sultone, 0.5% fluoroethylene carbonate, 1% vinyl sulfate, 0.5% tris(trimethylsilyl)phosphate, 0.5% methylene disulfonate, 8% 2-(dimethylphosphonate)-18-crown-6-ether.
[0089] Embodiment 2:
[0090] The anhydrous organic solvent used is: diethyl carbonate: ethyl methyl carbonate: ethylene carbonate = 30:40:30; lithium salt: 0.8M lithium hexafluorophosphate (LiPF6), 0.4M lithium bis(fluorosulfonyl)imide (LiFSI). Additives: 0.5% lithium difluorooxalatoborate, 0.5% lithium difluorophosphate, 0.3% lithium difluorobis(oxalatophosphate), 0.3% vinylene carbonate, 0.5% 1,3-propane sultone, 0.5% fluoroethylene carbonate, 1% vinyl sulfate, 0.5% tris(trimethylsilyl)phosphate, 0.5% methylene disulfonate, 5% 2-(dimethylphosphonate)-18-crown-6-ether.
[0091] Embodiment 3:
[0092] The anhydrous organic solvent used is: diethyl carbonate: ethyl methyl carbonate: ethylene carbonate = 30:40:30; lithium salt: 0.8M lithium hexafluorophosphate (LiPF6), 0.4M lithium bis(fluorosulfonyl)imide (LiFSI). Additives: 0.5% lithium difluorooxalatoborate, 0.5% lithium difluorophosphate, 0.3% lithium difluorobis(oxalatophosphate), 0.3% vinylene carbonate, 0.5% 1,3-propane sultone, 0.5% fluoroethylene carbonate, 1% vinyl sulfate, 0.5% tris(trimethylsilyl)phosphate, 0.5% methylene disulfonate, 1% 2-(dimethylphosphonate)-18-crown-6-ether.
[0093] The lithium ion batteries assembled in the above comparative examples and embodiments were tested at room temperature (25°C) and in the voltage range of 2.75-4.5V, with a 1 / 3C discharge test to determine the constant capacity. The 2C charge capacity (%) = 2C charge capacity / 1C discharge capacity, and the 3C discharge capacity (%) = 3C discharge capacity / 1C discharge capacity. The results are shown in Table 1:
[0094] Table 1 Short-term performance test
[0095] Liquid retention / g Fixed capacity / Ah First efficiency 2C charging 3C discharge Comparative Example 1 140.7 60.29 78.6% 35.1% 30.2% Comparative Example 2 140.3 60.99 77.6% 67.1% 69.6% Comparative Example 3 141.0 60.97 92.2% 89.2% 84.5% Example 1 140.7 60.14 92.4% 92.9% 95.0% Example 2 140.5 60.56 92.4% 93.9% 95.3% Example 3 140.9 60.97 92.2% 94.3% 96.6%
[0096] The lithium-ion batteries assembled in the above comparative examples and embodiments were tested for capacity at 1C or 1 / 3C discharge in the range of -30°C to 55°C, with a voltage range of 2.75 to 4.5V. The gas production of the battery was observed, and the battery was disassembled after low-temperature discharge to observe the pole pieces. The results are shown in Table 2:
[0097] Table 2 High and low temperature discharge performance test
[0098]
[0099]
[0100] The lithium-ion batteries assembled in the comparative example and the embodiment were stored at 100% SOC for 7 days at 55°C, and the capacity retention rate and recovery rate were tested in the voltage range of 2.75 to 4.5 V. The gas generation and lithium precipitation of the battery were observed, and the results are shown in Table 3:
[0101] Table 3 High temperature charging performance test
[0102] Capacity retention rate Capacity recovery rate Lithium Separation Gas production Comparative Example 1 26.4% 24.2% Lithium Separation Gas production Comparative Example 2 68.3% 63.7% Lithium Separation Gas production Comparative Example 3 86.7% 81.0% Lithium Separation Gas production Example 1 93.8% 97.2% No lithium precipitation No gas production Example 2 95.0% 98.9% No lithium precipitation No gas production Example 3 95.0% 99.6% No lithium precipitation No gas production
[0103] The lithium-ion batteries assembled in the comparative example and the embodiment were stored at 100% SOC for 28 days at 25°C, and the capacity retention rate and recovery rate were tested in the voltage range of 2.75 to 4.5 V. The gas generation and lithium precipitation of the battery were observed, and the results are shown in Table 4:
[0104] Table 4 Room temperature charging performance test
[0105] Capacity retention rate Capacity recovery rate Lithium Separation Gas production Comparative Example 1 22.9% 24.4% Lithium Separation Gas production Comparative Example 2 69.4% 67.9% Lithium Separation Gas production Comparative Example 3 87.7% 88.9% Lithium Separation Gas production Example 1 95.3% 98.0% No lithium precipitation No gas production Example 2 96.9% 99.9% No lithium precipitation No gas production Example 3 97.1% 100.8% No lithium precipitation No gas production
[0106] The lithium-ion batteries assembled in the comparative example and the embodiment were placed in an environment of 45°C and cycled at 1C charge and 1C discharge to test the capacity retention rate in a voltage range of 2.75 to 4.5 V. The lithium deposition of the batteries was observed, and the results are shown in Table 5:
[0107] Table 5 High temperature cycle performance test
[0108]
[0109]
[0110] The lithium-ion batteries assembled in the comparative example and the embodiment were placed in an environment of 25°C and cycled at 1C charge and 1C discharge to test the capacity retention rate in a voltage range of 2.75 to 4.5 V. The lithium deposition of the batteries was observed, and the results are shown in Table 6:
[0111] Table 6 Normal temperature cycle performance test
[0112] 100 laps 200 laps 300 laps 400 laps 500 laps Lithium Separation Gas production Comparative Example 1 28.2% 15.8% 12.5% 0.0% 0.0% Lithium Separation Gas production Comparative Example 2 66.1% 55.0% 52.6% 31.5% 14.5% Lithium Separation Gas production Comparative Example 3 81.9% 80.6% 67.6% 57.6% 34.0% Lithium Separation Gas production Example 1 98.2% 96.1% 94.4% 92.2% 90.7% No lithium precipitation No gas production Example 2 99.2% 97.4% 96.0% 93.1% 92.0% No lithium precipitation No gas production Example 3 100.7% 98.0% 96.3% 94.9% 92.3% No lithium precipitation No gas production
[0113] The lithium-ion batteries assembled in the above comparative examples and embodiments were subjected to a needle puncture test at 25°C and 100% SOC. The results are shown in Table 7:
[0114] Table 7 Acupuncture test
[0115] acupuncture Comparative Example 1 Fire Comparative Example 2 Fire Comparative Example 3 Fire Example 1 No fire Example 2 No fire Example 3 No fire
[0116] From the results, it can be seen that the high energy density lithium ion battery electrolyte with 2-(dimethyl phosphate)-18-crown-6-ether added to the electrolyte can improve its initial efficiency, rate performance, -30℃~55℃ high and low temperature discharge performance, storage performance, cycle performance and safety performance when working at 4.5V for lithium ion batteries, and has a good application prospect in high energy density systems.
[0117] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A lithium ion battery electrolyte additive, characterized in that: The additive includes 2-(dimethylphosphonate)-18-crown-6-ether as shown in Formula I:
2. A method for synthesizing a lithium ion battery electrolyte additive as claimed in claim 1, characterized in that: The method comprises the following steps: adding 18-crown-6-ether, N-bromosuccinimide and carbon tetrachloride into a dry reaction flask; then adding an initiator; heating the reaction mixture to reflux under nitrogen protection; during the reaction, N-bromosuccinimide generates bromine free radicals under the action of the initiator, and the bromine free radicals selectively react with a carbon on 18-crown-6-ether to generate 18-crown-6-ether-Br and succinimide; adding 18-crown-6-ether-Br, dimethyl phosphate potassium salt into the dry reaction flask; and , a phase transfer catalyst and an organic solvent; under stirring, heating the reaction mixture to 60-80°C for reaction; under the action of the phase transfer catalyst, the phosphate anion in the potassium dimethyl phosphate reacts with the bromine atom in 18-crown-6-ether-Br to undergo nucleophilic substitution reaction to generate 2-(dimethylphosphate)-18-crown-6-ether and potassium bromide; after the reaction, cooling the reaction mixture to room temperature; extracting and combining the organic phases, drying and purifying to obtain pure 2-(dimethylphosphate)-18-crown-6-ether.
3. A method for synthesizing a lithium ion battery electrolyte additive as claimed in claim 2, further characterized in that the initiator is azobisisobutyronitrile; the phase transfer catalyst is tetrabutylammonium bromide; the molar ratio of 18-crown-6-ether-Br to dimethyl phosphate potassium salt is 1:1.1-1.2, and the amount of the phase transfer catalyst is 0.1-0.2 times the amount of 18-crown-6-ether-Br substance.
4. A method for synthesizing a lithium ion battery electrolyte additive as claimed in claim 2 or 3, further characterized in that the purification is carried out by column chromatography: silica gel is selected as the stationary phase, ethyl acetate-petroleum ether mixed solvent is selected as the eluent, the volume ratio of the two is adjusted to 1:5-1:3, and TLC monitoring is performed to collect the fractions containing the target product to obtain pure 2-(dimethylphosphate)-18-crown-6-ether.
5. A lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether, characterized in that: The components of the electrolyte include lithium salt, an anhydrous organic solvent, and an electrolyte additive; wherein the electrolyte additive includes 2-(dimethyl phosphate)-18-crown-6-ether; and the amount of 2-((dimethyl phosphate)-18-crown-6-ether in the electrolyte is 0.1%-10% of the total mass of the electrolyte.
6. A lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether as claimed in claim 5, further characterized in that the amount of 2-(dimethylphosphate)-18-crown-6-ether in the electrolyte is 0.1%-5% of the total mass of the electrolyte, and more preferably 0.1%-2%.
7. A lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether as claimed in claim 5 or 6, characterized in that: The amount of the electrolyte additive accounts for 0.1% to 20% of the total mass of the lithium ion battery electrolyte.
8. A lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether as claimed in claim 5 or 6, characterized in that: In addition to 2-(dimethylphosphate)-18-crown-6-ether, the other additives are selected from at least one of fluoroethylene carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, tris(trimethylsilyl)phosphate, 1,3-propylene sultone, ethoxypentafluorocyclotriphosphazene, tetravinylsilane, fluorobenzene, tripropargyl phosphate, dicyclohexylcarbodiimide, lithium difluorophosphate, lithium difluorooxalatoborate, and lithium difluorobisoxalatephosphate.
9. A lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether as claimed in claim 5 or 6, characterized in that: The concentration of the lithium salt in the electrolyte is 0.8M-1.4M; the lithium salt is selected from at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
10. A lithium ion battery electrolyte containing 2-(dimethylphosphate)-18-crown-6-ether as claimed in claim 5 or 6, characterized in that: The anhydrous organic solvent includes at least one of carbonate and fluorinated solvent.
Citation Information
Patent Citations
Lithium manganese iron phosphate battery electrolyte
CN116344943A
Lithium ion battery electrolyte based on crown ether additive and lithium ion battery
CN118099522A
Crown ether compound, rechargeable battery electrolyte and rechargeable battery
CN118745164A
Cited By
Electrolyte additive for lithium metal battery, preparation method of electrolyte additive, lithium metal battery electrolyte and lithium metal battery
CN122482965A
An electrolyte additive for a lithium metal battery, a preparation method thereof, a lithium metal battery electrolyte, and a lithium metal battery
CN122482965B